PENGEMBANGAN MODUL PEMBELAJARAN IPAS DENGAN PENDEKATAN SAINTIFIK UNTUK MENUMBUHKAN KEMAMPUAN BERPIKIR TINGKAT TINGGI (HOTS) SISWA KELAS V SD - Deswita Suryani Sitanggang; Agnes Herlina Dwi Hadiyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Learning Science and Social (IPAS) that appears abstract in primary education is often considered one of the reasons for the low level of students' thinking, resulting in learning outcomes that do not meet expectations. A learning approach focused solely on understanding concepts without encouraging high-order thinking skills (HOTS) often leads to students being less trained in analyzing, evaluating, and creating. High-order thinking skills (HOTS) are the abilities that hone an individual's thinking through activities of analyzing, evaluating, and creating something. One effort to foster students' high-order thinking skills (HOTS) is the use of learning modules. This study aims to develop IPAS learning modules using a scientific approach to foster students' high-order thinking skills (HOTS) and describe the quality of IPAS learning modules for Grade V elementary school students. The research method used is Research and Development (R&D) of the ADDIE type. Data collection techniques used are qualitative and quantitative. Qualitative data analyze observations and interviews, while quantitative data process questionnaire and test data. Modules are developed by considering HOTS components, the scientific approach, and IPAS learning. The results show that IPAS learning modules can enhance students' high-order thinking skills (HOTS) through learning activities, producing module quality rated as "Very Good" with an average score of 3.81 from content experts and practitioners. Additionally, there is an improvement in students' high-order thinking skills (HOTS) as indicated by an average percentage increase in pretest and posttest scores of 81.77%.